Expression of human HIPKs in Drosophila demonstrates their shared and unique functions in a developmental model. - Kinsey, S.D.; Vinluan, J.P.; Shipman, G.A.; Verheyen, E.M. (G3 : genes - genomes - genetics, 2021)
Homeodomain-interacting protein kinases (HIPKs) are a family of four conserved proteins essential for vertebrate development, as demonstrated by defects in the eye, brain, and skeleton that culminate in embryonic lethality when multiple HIPKs are lost in mice. While HIPKs are essential for development, functional redundancy between the four vertebrate HIPK paralogues has made it difficult to compare their respective functions. Because understanding the unique and shared functions of these essential proteins could directly benefit the fields of biology and medicine, we addressed the gap in knowledge of the four vertebrate HIPK paralogues by studying them in the fruit fly Drosophila melanogaster, where reduced genetic redundancy simplifies our functional assessment. The single hipk present in the fly allowed us to perform rescue experiments with human HIPK genes that provide new insight into their individual functions not easily assessed in vertebrate models. Furthermore, the abundance of genetic tools and established methods for monitoring specific developmental pathways and gross morphological changes in the fly allowed for functional comparisons in endogenous contexts. We first performed rescue experiments to demonstrate the extent to which each of the human HIPKs can functionally replace Drosophila Hipk for survival and morphological development. We then showed the ability of each human HIPK to modulate Armadillo/?-catenin levels, JAK/STAT activity, proliferation, growth, and death, each of which have previously been described for Hipks, but never all together in comparable tissue contexts. Finally, we characterized novel developmental phenotypes induced by human HIPKs to gain insight to their unique functions. Together, these experiments provide the first direct comparison of all four vertebrate HIPKs to determine their roles in a developmental context.